Barriers to European cross-border E-commerce - Alexander Coad; Néstor Duch-Brown (European Commission, Joint Research Centre (JRC), 2017)
We analyse survey data to investigate the main barriers to European cross-border e-commerce. We investigate the determinants of selling online, as well as the frequency and determinants of cross-border e-commerce, and the role of barriers. Large firms, which are part of a group, are more likely to sell online. Firms generally make most of their online sales to their home country, although EU firms are more likely to engage in cross-border online trade with EU countries than non-EU countries. Firms report that they are facing a variety of barriers to e-commerce. Regulatory barriers are negatively associated with online sales. There is weak evidence that firms which use their own websites are more vulnerable to financial, market and information barriers. Firms that use a large platform experience fewer financial and market barriers. On the positive side, we find that small and young firms do not seem to be more vulnerable to barriers than large or more experienced firms.
Keywords: D23; K11; K12; L86; 330; digital single market; e-commerce; cross-border trade